INSTITUTE SUPERVISION AS AN EFFECTIVE TOOL OF INSTITUTIONALIZATION IN THE SOCIAL SERVICES OF KAZAKHSTAN - Lyaziza G. Adilova; Gulnara A. Abitova (International Journal of Innovative Technologies in Social Science, 2019)
The paper presents issues on institutionalization of the social services sphere in Kazakhstan in the framework of social modernization. In particular, it is the issue of increasing professionalism of social workers and supervisory support of specialists who works in special social services. Sociological surveys were conducted using a questionnaire surveys, interviews of experts, social workers. The institutional approach to increasing professionalism and competence of social workers, as well as an effectiveness of social work, was investigated on the basis of public opinion analyses. Based on the results of the empirical and sociological-statistical studies, the most critical factors of social service work have been identified and substantiated. Kazakhstan model of professional support to the provision of special social services is seen in the design of a new institutional model as Cross-Functional Institute of Supervision. This study contributes to optimization of the social work system and effectiveness of social services in future.